2014
DOI: 10.5424/fs/2014231-04521
|View full text |Cite
|
Sign up to set email alerts
|

Species richness of vascular plants along the climatic range of the Spanish dehesas at two spatial scales

Abstract: Aims of study: The goals of this paper are to summarize and to compare plant species richness and floristic similarity at two spatial scales; mesohabitat (normal, eutrophic, and oligotrophic dehesas) and dehesa habitat; and to establish guidelines for conserving species diversity in dehesas.Area of study: We considered four dehesa sites in the western Peninsular Spain, located along a climatic and biogeographic gradient from north to south. Main results: Average alpha richness for mesohabitats was 75.6 species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Diversity values in eutrophic communities on valley bottoms were much lower, as expected due to the negative effect of grazing pressure, and maximal diversity values are associated with intermediate levels of grazing pressure. López-Carrasco et al [38] found a different pattern in same-sized plots (0.50 × 0.50 m): sites in valley bottoms had higher species richness values than higher zones on hilltops, while del Barrio et al [64] obtained similar results on large plots (1000 m 2 ). Here, grazing intensity plays an important role in the variation of species richness, which reaches a maximum with intermediate levels of disturbance; this factor may predominate over topography and the fertility gradient.…”
Section: Topographymentioning
confidence: 93%
“…Diversity values in eutrophic communities on valley bottoms were much lower, as expected due to the negative effect of grazing pressure, and maximal diversity values are associated with intermediate levels of grazing pressure. López-Carrasco et al [38] found a different pattern in same-sized plots (0.50 × 0.50 m): sites in valley bottoms had higher species richness values than higher zones on hilltops, while del Barrio et al [64] obtained similar results on large plots (1000 m 2 ). Here, grazing intensity plays an important role in the variation of species richness, which reaches a maximum with intermediate levels of disturbance; this factor may predominate over topography and the fertility gradient.…”
Section: Topographymentioning
confidence: 93%